Directional selection for flowering time leads to adaptive evolution in Raphanus raphanistrum (Wild radish) - Ashworth, Michael B. (2016)
Fil: Ashworth, Michael B. The University of Western Australia. School of Plant Biology. Australian Herbicide Resistance Initiative. Crawley, WA, Australia.